Sibutramine (Reductil®)-Induced Cutaneous Leukocytoclastic Vasculitis: A Case Report - Ha, You Jin (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
A 24-year old woman presented with hemorrhagic vesicles on her legs. She had taken sibutramine (Reductil®, Abbott Labs., Seoul, South Korea) for 3 months and developed skin lesions the week before. A skin biopsy showed leukocytoclastic vasculitis with conspicuous eosinophilic infiltration of the tissue. These lesions showed improvement after discontinuation of sibutramine. However, 3 months later the skin lesions recurred on other sites on the lower extremities when the patient was rechallenged with the same drug for 2 weeks. Herein, we report the first case of necrotizing vasculitis induced by sibutramine.